Partido Comunista Português - P.C.P. - centro de trabalho - Amadora
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Arbeiterbewegung politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Kommunismus